CULTURE AND PSYCHOLOGY OF COMMUNICATION IN TEACHER PEDAGOGICAL ACTIVITY (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
The article examines the role of teachers’ communicative culture and psychology in enhancing students’ motivation and engagement through speech culture, emotional stability, and communicative competence.